Islamic universalism : a case study of Al-Biruni's thought - Flynn, Shafiq Ali (2015)
This research offers a new lens through which al-al-Biruni's scholarship can be perceived. It provides an understanding of his broader analytical framework which has hitherto only been alluded to in passing by such persons the likes of Rosenthal and Lawrence among others. Drawing from a textual analysis of al-Bīrūnī's works ranging from his earliest to last, the thesis maps and attempts to give body to the pervading quality of universalism intrinsic to the corpus al-Birunicum. The study engages al-Biruni from three distinct yet necessarily interrelated trajectories. We begin with the socio-historical whereby we argue that al-Biruni approached the study of the Hindu civilisation not as a reaction to the political strategy pursued by Sultan Maḥmūd, but more so as a means to provide an Islamic intellectual understanding of Hinduism to learned Muslims. In this, we conclude that the interpretations of Sultan Maḥmūd's governance, especially towards the Hindus has coloured the ways in which al-Bīrūnī and his Kitāb al-Hind have been understood, and that for the most part, the far majority of historical representations of Sultan Maḥmūd have had significant political overtones culminating in a strategic misapprehension of Maḥmūd and by extension al-Bīrūnī. Following this, the thesis examines the axiological bases and theological foundations for a case of Islamic universalism from al-Biruni's scholarship. Here, we argue that within the broader theme of axiology, al-Biruni's deontological discourse in the introduction of his Kitab al-Hind was unprecedented in the study of religion and civilisations, and represents a truly Islamic spirit to civilisational expansion. The thesis concludes by extending the same set of eudemonic values that emphasise the moral courage to accept reason over desire to an aspect of al-Biruni's engagement with the scientific enterprise. Through a distinction between astronomy and astrology coupled with al-Biruni's criticism of Aristotelian astral physics, the thesis argues that the language of neutral science is an important aspect in any discourse on universalism. In this discussion, a preliminary case for an Islamic humanism is argued. Not only do we believe that this thesis will encourage a new perspective on how al-Bīrūnī and the Islamic civilisation is understood, it has a clear relevance to contemporary issues, especially those troubling the West, concerning cultural integration, immigration, and conflict management, among others.